PENGGUNAAN METODE ESTAFET LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH METODE NUMERIK - Heri Herwanto (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
The purpose of this study was to determine the effect of the application of estafet learning method to improve students' critical thinking skills, increase student learning outcomes, to determine the relationship of critical thinking to student learning outcomes and to determine the responses of students about the application of estafet learning method. This research is a quantitative research. The research instruments included test questions, observation sheets, and questionnaire sheets. The subjects in this study were students of the computer faculty of the fourth semester informatics engineering study program. Data analysis techniques used the gain test, correlation test and Likert scale analysis. The results showed an increase in critical thinking skills and learning outcomes in the medium category. The relationship between critical thinking skills and learning outcomes has a strong enough relationship in the very significant category. Student responses to the application of estafet learning method showed a positive response.